Staining characteristics of BCL-2, BAX, p53, p21, Ki-67 andC-erbB2 in thyroid carcinomas - Cobanoglu, Bengu; Ozercan, Mehmet Resat (Aves, 2007)
Purpose: This study aims at investigating the relation between papillary, follicular, medullar and anaplastic types of thyroid carcinomas and immunohistochemical markers such as bcl-2, bax, p53, p21, Ki-67, and c-erbB2. Material and Methods: A total of forty thyroid carcinoma cases, 10 of which were papillary, follicular anaplastic and medullar were applied bcl-2, bax, p53, p21, Ki 67, and c-erbB2 using immunohistochemistry. Results: Of these, positive staining was observed in all thyroid carcinoma types except for medullar carcinoma for bax, Bcl-2 showed 60% positive staining in papillary type, 80% in follicular type, 90% in medullar type and 60% in anaplastic type. The relation was that as tumor differentiation decreased positive staining increased both for p21 and p53. None of the medullar carcinoma cases had positive staining with these markers. While Ki-67 index was found to be low in the papillary and follicular carcinomas it was found to be significantly high in the medullary and anaplastic carcinomas.The positivity, which was 60% in the papillary carcinomas, reached 80% in anaplastic and 90% in the medullary carcinomas, with cerbB2. Conclusion: It was established that the relation between thyroid carcinomas and bax, bcl-2 and c-erbB-2 was not significant, while their relation to p21,p53 and Ki67 showed a significant difference between well-differentiated and poor-differentiated tumors.
Keywords: Apoptasis; Thyroid carcinoma